2022
DOI: 10.3934/mbe.2022220
|View full text |Cite
|
Sign up to set email alerts
|

A novel immune checkpoint-related gene signature for hepatocellular carcinoma to predict clinical outcomes and therapeutic response

Abstract: <abstract> <p>Immune checkpoint genes (ICGs) have recently been proven to perform instrumental functions in the maintenance of immune homeostasis and represent a promising therapeutic strategy; however, their expression patterns and prognostic values are not fully elucidated in hepatocellular carcinoma (HCC). In this investigation, we focused on establishing and validating a prognostic gene signature to facilitate decision-making in clinical practice. Clinical information, as well as transcripto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…In this study, we found that patients with high MTMR2 expression had higher stromal scores and tumor purity scores. Tumor stromal cell infiltration is an important factor promoting the progression of HCC 29 , 30 . Further immune infiltration analysis showed that MTMR2 is significantly correlated with the infiltration levels of CD4+ memory resting T cells and activated dendritic cells, and is positively correlated with immune checkpoint markers CD276, LGALS9, TNFSF15, VTCN1, and HAVCR2 ( p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that patients with high MTMR2 expression had higher stromal scores and tumor purity scores. Tumor stromal cell infiltration is an important factor promoting the progression of HCC 29 , 30 . Further immune infiltration analysis showed that MTMR2 is significantly correlated with the infiltration levels of CD4+ memory resting T cells and activated dendritic cells, and is positively correlated with immune checkpoint markers CD276, LGALS9, TNFSF15, VTCN1, and HAVCR2 ( p < 0.05).…”
Section: Discussionmentioning
confidence: 99%